Differences in serum immunoglobulin g1 and total protein concentrations in neonatal calves on days 1, 5, and 10 - Wankel, L.E.; Marston, T.T.; Stokka, Gerald L.; Rozell, Timothy G. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Immunoglobulin G1 (IgG1) serum concentrations are used to evaluate passive transfer of immunity in neonatal calves. Total serum proteins also can be measured to evaluate calf health. If IgG1 and total serum protein concentrations change with age, it becomes imperative to compare samples only from a narrow time period. Otherwise, differences might be due to age and not immune status. To help define this time period, blood was drawn from 10 beef calves when they were 1, 5, and 10 days of age. Serum samples were analyzed for IgG1 and total protein concentrations. Total protein concentrations decreased from days 1 to 5 (P<.05) or days 1 to 10 (P<.05), but not from days 5 to 10 (P=.46). IgG1 concentrations declined from days 1 to 10 (P<.05), but values from days 1 to 5 were similar (P=.17). Thus, it is important to collect serum on day 1 to guarantee correct results when evaluating IgG1 and total proteins collectively. However, if IgG1 alone is evaluated, serum can be collected between days 1 and 5.
Keywords: Beef; Immunoglobulin G1; Total protein; Calves